Geographic and socioeconomic influence on knowledge and practices related to antimicrobial resistance among smallholder pig farmers in Uganda - Access to services and drugs, and practices and knowledge related to antimicrobial resistance, among smallholder pig farmers in Uganda - Magnusson, Ulf; Mainack Dione, Michel (Swedish University of Agricultural Sciences, 2022)
To mitigate the development of antimicrobial resistance (AMR), antibiotic use (ABU) in the livestock sector needs to be reduced. In low- and middle-income countries, regulations have shown to be less successful in reducing ABU. Here, a bottom-up approach can complement legal frameworks which requires an understanding of the drivers for ABU. In this study, we investigated the influence of geographic and socioeconomic settings on determinants for ABU among pig farmers in Uganda. The data was collected through a questionnaire (containing 75 questions) in two districts, Lira and Mukono, and comparative statistical analyses were performed. Farmers in Lira had lower access to animal health services, applied disease preventive measures less and used antibiotics more. In Mukono, it was more common to consult a veterinarian in response to disease, while it in Lira was more common to consult an animal health worker. There was no difference in how many that followed treatment instructions from a veterinarian, but it was more common in Lira to follow instructions from pharmacies. The findings support the need for locally tailored AMR-reducing interventions to complement regulations. To accomplish this tailoring, systematic collection of knowledge of farm structures, farm practices and access to animal health services and veterinary drugs is necessary.

The questionnaire was administered and recorded electronically on tablets using Open Data Kit (ODK) (https://getodk.org), an open-source tool for smart devices (i.e., smartphone or tablet) that enables creation and use of electronic questionnaires. The data collection through ODK was backed up daily.

The dataset contains 72 columns and 463 rows.

For explanations of the variables, see the separate file "AMUSE_Uganda_2022_dataset_Explanations". For explanations of the answer options, see the separate file "AMUSE_Uganda_2022_Questionnaire".

För att sakta ner utvecklingen av antimikrobiell resistens (AMR) så behöver antibiotikaanvändningen i produktionsdjurssektorn minska. I låg- och medelinkomstländer har regulatoriska ramverk visat sig mindre användbara för att minska antibiotikaanvändningen. Här kan en "nerifrån-upp"-strategi komplettera regulatoriska ramverk; vilket kräver en förståelse för vad som driver antibiotikaanvändningen. I den här studien har vi undersökt påverkan av geografiska och socioekonomiska förhållanden på några avgörande faktorer för antibiotikaanvändning bland grisuppfödare i Uganda. Datan samlades in via en enkät (innehållande 75 frågor) i två distrikt, Lira och Mukono, och komparativa statistiska analyser genomfördes. Bönder i Lira hade lägre tillgång till djurhälsotjänster, använde sjukdomsförebyggande åtgärder i lägre utsträckning och använde antibiotika till sina grisar mer frekvent. I Mukono var det vanligare att konsultera en veterinär vid sjukdom hos grisarna, medan det i Lira var vanligare att konsultera en djurhälsoarbetare (ej veterinär). Ingen skillnad kunde detekteras gällande hur många som följde behandlingsinstruktioner från en veterinär, men det var vanligare i Lira än i Mukono att följa instruktioner från ett apotek. Fynden stödjer att det finns ett behov av lokalt skräddarsydda AMR-reducerande interventioner som ett komplement till regelverk. För att kunna skräddarsy interventionerna är det nödvändigt med systematisk ihopsamling av kunskap om gårdstruktur, bönders praktik samt tillgång till djurhälsotjänster och veterinärmedicinska läkemedel.

Enkäten administrerades och sparades elektroniskt på läsplattor via Open Data Kit (ODK) (https://getodk.org), ett open-source verktyg för smarta enheter (t.ex. smartphone eller läsplatta) som möjliggör skapande och användning av elektroniska enkäter.

Datasetet innehåller 72 kolumner och 463 rader.

För förklaring av variabler se "AMUSE_Uganda_2022_dataset_Explanations", för förklaring av svarsalternativ se enkäten "AMUSE_Uganda_2022_Questionnaire".
Geografisk och socioekonomisk påverkan på kunskap och praktik relaterad till antibiotikaresistens bland småbrukande grisuppfödare i Uganda - Tillgång till tjänster och läkemedel, samt praktik och kunskap relaterad till antimikrobiell resistens, hos grisuppfödare i Uganda
Keywords: Public Health; Folkhälsa; Drug Resistance, Microbial; Resistens mot antimikrobiella läkemedel; antibiotic; antibiotika; farmer knowledge; bönders kunskap; antibiotic resistance; antibiotikaresistens; smallholders; småbrukare; antibiotic use; antibiotikaanvändning; farm practices; bönders agerande; Uganda; Uganda; Veterinary Science; Veterinärmedicin; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin